Maxillary sinus infection caused by the homobasidiomycetous fungus Schizophyllum commune. - Kern, M E (1986)
We investigated a case of maxillary sinus infection caused by the medusoid mutant of the basidiomycetous fungus Schizophyllum commune. Morphologies of both typical and medusoid forms of S. commune were determined. Prior reports of pathogenic homobasidiomycetes are discussed.